Towards a long term development vision for Bangladesh: some socioeconomic and legal aspects - Jalil, Md. Abdul; Islam, Md. Saidul (Canadian Center of Science and Education, 2010)
Following modernization paradigm and some local dynamics conducive to development, some Asian countries emerged as economic tigers in the world. Conversely, other Asian countries including Bangladesh failed to taste economic development despite having monetary and technological aids from some developed nations. Drawing on some social and historical trajectories of the divergent contours of Asian development/ underdevelopment, the paper examines the state of development in Bangladesh. The study has found that Japan is the first country in Asia to achieve modernization, and it was followed by other Asian tigers such as Korea, Taiwan, Singapore, Malaysia and currently China and India. We found that all these Asian tigers exert a developmental model which is characterized by ‘endogenous’ modernity and economic nationalism largely driven by, among other things, long-term economic vision and strong political leadership. While the history of Bangladesh has witnessed various cultural nationalisms, the nation has failed to generate any unified economic nationalism since its independence in 1971. We suggest that Bangladesh needs a long-term development vision—a key thrust for economic nationalism—focusing more on some socioeconomic and legal aspects that have historically become major impediments for development.